Popular support for legislatures in Asia. Issue 2 (3rd April 2019) - Sanborn, Howard
ABSTRACT: Legislatures have long served as the fundamental organ of democratic rule. They bring together disparate views and competing preferences in one venue as an effort to introduce a equitable means of compromise to produce policies that affect those whom legislatures represent. They also check the authoritarian tendencies of other government actors, notably the executive, and create the conditions for institutionalised, rather than violent, debate. The legislatures of democratic Asia are no different. In this paper, I evaluate popular support for assemblies across the democracies of Asia, in terms of their legitimacy and use as a check on power. Traditional measures of support, including age, education, and liberal values, indicate growing support for legislatures. However, the significant effects of economic evaluations and the limited attachment to political parties suggest that the legislatures of Asia are still far from consolidating their role as assemblies that support democratic regimes in the region.